Neurospora Clock-Controlled Gene 9 (ccg-9) Encodes Trehalose Synthase: Circadian Regulation of Stress Responses and Development - Shinohara, Mari L. (American Society for Microbiology, 2002)
The circadian clock of Neurospora crassa regulates the rhythmic expression of a number of genes encoding diverse functions which, as an ensemble, are adaptive to life in a rhythmic environment of alternating levels of light and dark, warmth and coolness, and dryness and humidity. Previous differential screens have identified a number of such genes based solely on their cycling expression, including clock-controlled gene 9 (ccg-9). Sequence analysis now shows the predicted CCG-9 polypeptide to be homologous to a novel form of trehalose synthase; as such it would catalyze the synthesis of the disaccharide trehalose, which plays an important role in protecting many cells from environmental stresses. Consistent with this, heat, glucose starvation, and osmotic stress induce ccg-9 transcript accumulation. Surprisingly, however, a parallel role in development is suggested by the finding that inactivation of ccg-9 results in altered conidiophore morphology and abolishes the normal circadian rhythm of asexual macroconidial development. Examination of a clock component, FRQ, in the ccg-9-null strain revealed normal cycling, phosphorylation, and light induction, indicating that loss of the conidiation rhythm is not due to changes in either the circadian oscillator or light input into the clock but pointing instead to a defect in circadian output. These data imply an interplay between a role of trehalose in stress protection and an apparent requirement for trehalose in clock regulation of conidiation under constant environmental conditions. This requirement can be bypassed by a daily light signal which drives a light-entrained rhythm in conidiation in the ccg-9-null strain; this bypass suggests that the trehalose requirement is related to clock control of development and not to the developmental process itself. Circadian control of trehalose synthase suggests a link between clock control of stress responses and that of development.